2014
DOI: 10.3389/fnana.2014.00082
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of the calretinin-expressing progenitors in the human cerebral cortex

Abstract: The complex structure and function of the cerebral cortex critically depend on the balance of excitation and inhibition provided by the pyramidal projection neurons and GABAergic interneurons, respectively. The calretinin-expressing (CalR+) cell is a subtype of GABAergic cortical interneurons that is more prevalent in humans than in rodents. In rodents, CalR+ interneurons originate in the caudal ganglionic eminence (CGE) from Gsx2+ progenitors, but in humans it has been suggested that a subpopulation of CalR+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 88 publications
(148 reference statements)
4
24
0
Order By: Relevance
“…Furthermore, human RGCs express growth factor PDGFD and its receptor, which is not observed in mice ( Lui et al, 2014 ). Supporting evidence is also obtained in vitro from modeling human cortical development using induced pluripotent stem cells ( Mariani et al, 2012 ), human embryonic stem cells ( Reinchisi et al, 2013 ), or enriched RGCs ( Radonjić et al, 2014b ; Yu and Zecevic, 2011 ). Recently, large-scale studies of genes involved in cortical development have shown considerable species-specific differences between humans and mice ( Kang et al, 2011 ; Miller et al, 2014 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, human RGCs express growth factor PDGFD and its receptor, which is not observed in mice ( Lui et al, 2014 ). Supporting evidence is also obtained in vitro from modeling human cortical development using induced pluripotent stem cells ( Mariani et al, 2012 ), human embryonic stem cells ( Reinchisi et al, 2013 ), or enriched RGCs ( Radonjić et al, 2014b ; Yu and Zecevic, 2011 ). Recently, large-scale studies of genes involved in cortical development have shown considerable species-specific differences between humans and mice ( Kang et al, 2011 ; Miller et al, 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Tissue was processed as previously described ( Radonjić et al, 2014b ). For detailed protocol and a list of antibodies, see the Supplemental Experimental Procedures and Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it remains a possibility that a small number of ASCL1 + progenitors may give rise to GABAergic neurons, particularly at later stages, where it has been reported that mRNA levels of ASCL1 increase dramatically between 16 and 19 PCW along with GSX2, a transcription factor important in the differentiation of calretinin‐positive interneurons of CGE origin (Radonjić et al. 2014b). Our RNAseq study only extended as far as 17 PCW but showed no trend towards a dramatic increase in ASCL1 expression towards mid‐gestation, although we did see a large increase in ASCL1 immunoreactive cells in the VZ in parts of the cortex at 19 PCW.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no molecular explanation for morphological differences in VIP + /CR + neocortical GABAergic neurons between rodents and primates. Indeed, although several studies have examined the origins and development of human GABAergic neurons (Bayatti et al 2008;Jakovcevski et al 2011;Radonjic et al 2014b;Al-Jaberi et al 2015), to our knowledge, no molecular differences between GABAergic neurons of rodents and primates have been described. Given the increasing appreciation for the role of GABAergic dysfunction in a variety of human neurodevelopmental disorders (Marin 2012;Southwell et al 2014), it is critical to understand the molecular bases of GABAergic neuron specification and maturation in the human brain (Clowry et al 2010;Molnar and Clowry 2012).…”
Section: Introductionmentioning
confidence: 99%